Current Understanding and Future Research Priorities in Malignancy Associated With Inborn Errors of Immunity and DNA Repair Disorders: The Perspective of an Interdisciplinary Working Group - Bomken, Simon; van der Werff Ten Bosch, Jutte; Attarbaschi, Andishe; Bacon, Chris M.; Borkhardt, Arndt; Boztug, Kaan; Fischer, Ute; Hauck, Fabian; Kuiper, Roland P.; Lammens, Tim; Loeffen, Jan; Neven, Bénédicte; et al. (Frontiers in Immunology, 2018)
Patients with inborn errors of immunity or DNA repair defects are at significant risk of developing malignancy and this complication of their underlying condition represents a substantial cause of morbidity and mortality. Whilst this risk is increasingly well-recognized, our understanding of the causative mechanisms remains incomplete. Diagnosing cancer is challenging in the presence of underlying co-morbidities and frequently other inflammatory and lymphoproliferative processes. We lack a structured approach to management despite recognizing the competing challenges of poor response to therapy and increased risk of toxicity. Finally, clinicians need guidance on how to screen for malignancy in many of these predisposing immunodeficiencies. In order to begin to address these challenges, we brought together representatives of European Immunology and Pediatric Haemato-Oncology to define the current state of our knowledge and identify priorities for clinical and research development. We propose key developmental priorities which our two communities will need to work together to address, collaborating with colleagues around the world.